Failure analysis and the cold crack formation mechanism for the QP1180 steel welded joint. (December 2021) - Ding, Kai; Wang, Yuanfang; Lei, Ming; Wei, Tao; Wu, Guanzhi; Zhang, Yuanheng; Pan, Hua; Gao, Yulai
Graphical abstract: Highlights: The formation of Widmanstätten caused the microhardness decrease in WM. The Widmanstätten could extended form WM into HAZ along the PAGBs. The cracks initiated at the interface between Widmanstätten and martensite. Abstract: Gas metal arc welding (GMAW) is applied to fabricate the QP1180 steel welded joint. The formation of the Widmanstatten ferrite (WF) in weld metal (WM) and its effect on the cold crack generation for QP1180 welded joint was systematically discussed. It is found that the inhomogeneous distribution of the WF can result in the lowest microhardness (∼275 HV) in the WM. High cooling rate, large grain size, low content of element C and high content of element Mn in the region near the WM together trigger the formation of WF, and their epitaxial growth can lead to their extension into the heat affected zone (HAZ) along the prior austenite grain boundaries. As a result, the micro-cracks are formed at the interface between the WF and martensite. Subsequently, the harder martensite with large size further promotes the propagation of the micro-cracks along the grain boundaries in the HAZ, forming the intergranular fracture eventually.